(untitled) (Revista Direitos Humanos e Democracia, 2026)
This essay aims to analyze the right to housing in the Covid-19 pandemic and its consequences, focusing on Brazilian families belonging to vulnerable classes experiencing housing insecurity. In this sense, to carry out this study, the fundamental rights of the Federal Constitution that permeate the topic, the Treaties, Pacts and Conventions to which Brazil is a signatory and which protect the right to housing, were developed. Continuously, the suspensions of evictions and removals imposed proposed by Federal Law nº 14.216/2021 and by the Claim of Non-Compliance with Fundamental Precept - ADPF nº 828 were investigated, in particular, the structuring decision contained in the fourth incidental provisional protection, questioning the regime of transition proposed from October 31, 2022, when the suspensions under Federal Law Nº 14.216/2021 are no longer in force. Finally, the importance of the structural process and structuring decisions for the effectiveness of fundamental rights will be demonstrated.